Performance Analysis of an IoT and Scada-Based Oil Tank Filling Monitoring System Using Omron PLC at PT Pertamina Patra Niaga Meulaboh - Ermando Sihombing; Solly Aryza; Beni Satria (INFOKUM, 2025)
The monitoring and control system in the oil tank filling process plays a crucial role in ensuring efficiency, safety, and accuracy in fuel distribution. This study aims to analyze the implementation of an IoT and SCADA-based monitoring system for oil tank filling using an Omron PLC at PT Pertamina Patra Niaga Meulaboh. The system integrates an Omron Programmable Logic Controller (PLC) as the main control unit, level sensors for real-time tank capacity detection, as well as IoT and Supervisory Control and Data Acquisition (SCADA) for remote monitoring. The research methodology includes system design, implementation, and testing, focusing on data communication reliability, sensor accuracy, and tank filling efficiency. The test results show that the system can monitor oil levels with an accuracy of ±0.5%, and improve operational efficiency by reducing filling errors by up to 20% compared to conventional methods. The implementation of IoT allows operators to access real-time filling data through a web-based dashboard, while SCADA provides more structured control over the filling process. The findings of this study conclude that the integration of IoT and SCADA in a PLC-based tank filling system significantly enhances efficiency, accuracy, and safety in oil filling operations. This technology holds great potential for broader application in the oil and gas industry to improve the effectiveness of fuel distribution systems.